Students’ Perspectives of Experiential Learning in an Addictions Course - Tammi F. Dice; Kristy Carlisle; Rebekah Byrd (Teaching and Supervision in Counseling, 2019)
Substance use disorder practitioners may identify as individuals in recovery, while others may have never experienced the challenge of abstinence. Without this lived experience, it may be difficult to accurately empathize with clients in recovery. Experiential learning is a way for students to live through an exercise in abstinence. The value of utilizing experiential learning for skill development and application of theory is established. However, there is no empirical research examining the use of experiential learning with undergraduate substance use disorder practitioner trainees not in recovery from addiction as a means to increase their ability to empathize with clients’ experiences. This article explored the impact of an experiential learning assignment in an undergraduate addictions course. A qualitative analysis of students’ written reflections revealed four primary themes. Authors offer suggestions for substance use disorder educators and recommendations for future research.
Keywords: addictions training; addictions course; experiential learning